Performance Evaluation of Cauliflower Cultivars in Mid-Hills of Nepal for Winter Season Production - Shrestha, Surendra Lal (Agriculture Development Journal, 2022)
Cauliflower (Brassica Oleracea botrytis) is one of the most popular and demanded vegetables in Nepal. Five cultivars: Barkha, Girija, Giewont, Whistler and Snow Mystique were transplanted in the first week of October 2016 and 2017 in the mid-hills (Kathmandu valley, 1300 masl) and grown during the winter season with 60X45 cm spacing. Source seed of Snow Mystique was Takii Seed Japan and the rest were Montsanto Seed, India. Crops were fertilized with 200:120:80N.P.K Kg/ha and 15-ton FYM/ha. Insecticide and fungicide were sprayed one time in the early period for crop establishment. The main objective of this experiment was to find out suitable high yielding and insect pest and disease tolerant hybrid cauliflower cultivars for commercial farming in the mid-hills of Nepal. Crops were evaluated with their vegetative, insect pest and disease, yield and farmers' and consumers' response in two consecutive years. Results showed that among the tested cultivars, Barkha was found to be highly uniform, vigorous, less attacked by insect pests and disease, early harvestable (62.7 days after transplanting), efficient per day yield (487.7 kg/ha), preferable average head weight (1039 g), freshness (4.3) and market preference (4.0) as compared to check variety Snow Mystique. On the other hand, Snow Mystique has only yield efficiency (436.2 kg/ha/day), greater insect damage and leaf spot disease, longer days to harvest (101 days), and freshness (3.8), respectively. Hence, Barkha has been selected and recommended for commercial cultivation in the mid-hills of Nepal.